2000
DOI: 10.1242/jeb.203.17.2565
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor Repertoire of The Larval Zebrafish: Swimming, Turning and Prey Capture

Abstract: Larval zebrafish (Brachydanio rerio) are a popular model system because of their genetic attributes, transparency and relative simplicity. They have approximately 200 neurons that project from the brainstem into the spinal cord. Many of these neurons can be individually identified and laser-ablated in intact larvae. This should facilitate cellular-level characterization of the descending control of larval behavior patterns. Towards this end, we attempt to describe the range of locomotor behavior patterns exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 418 publications
(83 citation statements)
references
References 70 publications
3
80
0
Order By: Relevance
“…C-starts were characterized by a large maximum tail amplitude and large bout integral (Burgess and Granato, 2007;Figure 4D, blue cluster). Burst swims exhibited a high tail beat frequency and were symmetric across the midline (Budick and O'Malley, 2000;Figure 4D, red cluster). Slow swims exhibited relatively small values across all three parameters (Figure 4D, green cluster).…”
Section: Inhibition Of the Ni Reduces The Number Of Wta Behavioral Re...mentioning
confidence: 99%
“…C-starts were characterized by a large maximum tail amplitude and large bout integral (Burgess and Granato, 2007;Figure 4D, blue cluster). Burst swims exhibited a high tail beat frequency and were symmetric across the midline (Budick and O'Malley, 2000;Figure 4D, red cluster). Slow swims exhibited relatively small values across all three parameters (Figure 4D, green cluster).…”
Section: Inhibition Of the Ni Reduces The Number Of Wta Behavioral Re...mentioning
confidence: 99%
“…When a zebrafish larva encounters a potentially edible object, it needs to switch its behavior from exploration, when it travels relatively large distances, to prey hunting in its immediate surroundings. Larvae hunt preys (in laboratory settings most often unicellular organisms such as paramecia, or small moving visual stimuli simulating them) with a well-coordinated series of fin, tail, eye, and jaw movements performed in sequential steps of prey detection, approach, and ingestion (Budick and O'Malley, 2000;Bianco et al, 2011;Preuss et al, 2014;Semmelhack et al, 2014;Antinucci et al, 2019;Mearns et al, 2020). By using a microscope capable of performing whole-brain calcium imaging at cellular resolution in freely swimming zebrafish larvae (Kim D. H. et al, 2017), Marques et al identified neuronal correlates of exploration and hunting behavior (Marques et al, 2020).…”
Section: Modulation Of Exploratory and Foraging Behaviorsmentioning
confidence: 99%
“…Moreover, methods for imaging and analyzing activity of a large number of neurons are lowering the barrier for discovering new neuromodulatory circuits (Ahrens et al, 2012;Freeman et al, 2014;Keller and Ahrens, 2015;Randlett et al, 2015;Lovett-Barron et al, 2017;Mu et al, 2020). Finally, zebrafish larvae perform several well-characterized behaviors (Budick and O'Malley, 2000;Orger and de Polavieja, 2017), some of which, such as hunting and threat avoidance, are modulated by internal states (De Marco et al, 2014Filosa et al, 2016;Lovett-Barron et al, 2017). The behavioral repertoire of older zebrafish is wider, including for example territoriality, social, and reproductive behavior (Orger and de Polavieja, 2017), but their larger and opticallyopaque brains constitute an obstacle for optical interrogation of neuronal circuits involved in neuromodulation.…”
Section: Introductionmentioning
confidence: 99%
“…However, at the 5 days post-fertilization larval life stage, when zebrafish are approximately 4 mm in length, before the onset of social shoaling behavior [25,26], they utilize different movement patterns from adult fish. Larval zebrafish, a millimeter with 2 Ls swimmer move in what is often termed a beat-and-glide or burstand-coast discontinuous manner; they swim in bouts of movement followed by pauses [27]. This species has been extensively studied in terms of their kinematics, neurobiology, development, and behavior [28][29][30][31][32] but the individual or collective motion of larvae in confinement has not been explored previously.…”
Section: Introductionmentioning
confidence: 99%